An integrated low-power Binary-PAM based wireless telemetry circuit for implantable cardiac pacemakers. (May 2020) - Xu, Jiangtao; Zhai, Yujian; Yang, Yang; Zhang, Ruizhi; Zhang, Hong
Abstract: A low-power wireless telemetry circuit integrated in an analog front-end (AFE) chip for implantable cardiac pacemakers is presented in this paper. With an on-chip telemetry circuit, the electrocardiogram (ECG) data can be transmitted directly from the AFE chip to a programmer outside the human body. Such a direct-memory-access (DMA) scheme improves data transmission efficiency and saves the overall power consumption. The proposed telemetry system employs a near-field inductive-coupling link with oscillating frequency of 128 ​kHz and a binary pulse-amplitude-modulation (PAM) strategy to achieve higher reliability. It consumes lower power and reach a longer communication distance when compared to conventional on-off-keying (OOK) modulation method. In order to further reduce the power consumption, pulse width adjustment technique is adopted in the transmitter. Also, edge detection and window detection techniques are employed in the receiver, making it more robust and immune to noise, disturbance and clock skew. The AFE chip is implemented using a 0.35-μm CMOS technology and the telemetry circuit occupies an active area of 1150umX350 ​μm. Measurement results show that the proposed wireless communication circuit can operate under a power supply range of 2.0–2.8 ​V, and achieves a maximum communication distance of 12 ​cm with current consumption lower than 26 ​μA and bit error rate less than 10 −5 .